1988
DOI: 10.1007/bf02549510
|View full text |Cite
|
Sign up to set email alerts
|

The morphological basis of ureteral peristalsis

Abstract: The ultrastructure of the normal rat ureter has been studied in order to correlate the morphological findings with the function of the organ. Electron microscopy demonstrates that the ureteral musculature behaves as a functional syncytium which permits the spread of electrical excitation from cell to cell. A scanty number of nerve endings without evidence of autonomic ganglia was found throughout the ureteral layers. These morphological data support the hypothesis that ureteral peristalsis is an essentially my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In the case of ureter smooth muscle, it has been demonstrated that it behaves as an electrical syncytium and is responsible for ureteral peristalsis. 21 The smooth muscle of the urethra is another example of syncytial tissue in this system. 22…”
Section: Syncytial Smooth Muscle Tissuesmentioning
confidence: 99%
“…In the case of ureter smooth muscle, it has been demonstrated that it behaves as an electrical syncytium and is responsible for ureteral peristalsis. 21 The smooth muscle of the urethra is another example of syncytial tissue in this system. 22…”
Section: Syncytial Smooth Muscle Tissuesmentioning
confidence: 99%
“…However, we have shown that ureteric division and re-anastomosis does lead to a significant increase in retrograde conduction of peristalsis waves. This is likely to be the consequence of surgical disruption of ureteric smooth muscle continuity and further supports an important role for myogenic conduction in ureteric peristalsis in man [2,3]. An alternative, if speculative, explanation is that the increased incidence of retrograde peristalsis is the consequence of loss of neural regulatory activity [a].…”
Section: Discussionmentioning
confidence: 94%
“…The pelvicalyceal system contains a source of pacemaker activity [ 11 which initiates ureteric peristalsis and thereafter both neural and smooth muscle activity are involved in the conduction of the peristalsis wave. Structural evidence from electron microscopy studies [2] together with evidence from functional studies following ureterolysis [ 31 suggests that the autonomic innervation of the ureter is not essential for the conduction of peristalsis but that it may nevertheless modulate peristalsis and influence ureteric tone [2]. In contrast, continuity of ureteric smooth muscle is necessary for antegrade conduction of peristalsis waves with disruption being associated with retrograde peristalsis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some of the investigators found longitudinal and/or circumferential orientations [2]–[8], [16], while others observed helical/interwoven SMC orientations [9], [15], [17], [20]. In rat ureter, similar discrepancies are found, i.e., some authors describe the rat ureter's LM as being layered with an outer longitudinal and an inner circular layer [21][23], whereas other groups describe no clear layering [10], [24], or an inner longitudinal and outer circular layer [25]. It is important to note that methodological aspects may play a role in these discrepancies.…”
Section: Introductionmentioning
confidence: 99%